2022
DOI: 10.3389/fphar.2022.1029601
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis of liver cancer and the therapeutic potential of bioactive substances

Abstract: Liver cancer is the third most common cause of cancer-related deaths in the world and has become an urgent problem for global public health. Bioactive substances are widely used for the treatment of liver cancer due to their widespread availability and reduced side effects. This review summarizes the main pathogenic factors involved in the development of liver cancer, including metabolic fatty liver disease, viral infection, and alcoholic cirrhosis, and focuses on the mechanism of action of bioactive component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 171 publications
0
5
0
Order By: Relevance
“…Polysaccharides are biologically active macromolecules composed of 10 or more monomers linked by glycosidic bonds. Extensive research has highlighted the therapeutic and ameliorative effects of natural polysaccharides on liver cancer, sourced from plants, animals, marine organisms, and fungi [ 7 ]. For instance, polysaccharides purified from Panax ginseng (PHP-1) and active polysaccharides from Ganoderma lucidum (GLPS) function as tumor immunotherapy modulators.…”
Section: Nps With Therapeutic Activity For Liver Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Polysaccharides are biologically active macromolecules composed of 10 or more monomers linked by glycosidic bonds. Extensive research has highlighted the therapeutic and ameliorative effects of natural polysaccharides on liver cancer, sourced from plants, animals, marine organisms, and fungi [ 7 ]. For instance, polysaccharides purified from Panax ginseng (PHP-1) and active polysaccharides from Ganoderma lucidum (GLPS) function as tumor immunotherapy modulators.…”
Section: Nps With Therapeutic Activity For Liver Cancermentioning
confidence: 99%
“…Nutrients 2024, 16, 1642 2 of 36 Natural products (NPs) exhibit diverse biological activities, including anti-inflammatory and antioxidant properties, rendering them promising sources for developing novel therapies for liver cancer [6,7]. Extensive in vitro and in vivo studies have unveiled the anti-tumor potential of NPs against liver cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The main risk factors for the development of liver cancer are long-term infection with the hepatitis B virus, hepatitis C virus, hepatitis D virus, nonalcoholic steatohepatitis, alcoholic cirrhosis, autoimmune hepatitis, type 2 diabetes, obesity, and consumption of food contaminated with alpha toxin B1. Gender, geographic region, and age may be associated with the occurrence of liver cancer (Gao et al, 2022).…”
Section: Cancer Cell Growthmentioning
confidence: 99%
“…Bioactive peptides are remarkable biomolecules with a wide spectrum of pharmacological functions, including anti-oxidant, antifungal, hypotensive, hypoglycemic, keratolytic, and sedative activities, which are encrypted in their sequences and released during digestion [7][8][9]. It has been reported that bioactive peptides have positive effects against alcohol induced liver damage [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%